Influenza vaccination: vital shield against asthma exacerbations - Ismail, Hammad; Muhammad Usman Baig,; Maryam Nawaz, (Journal of the Pakistan Medical Association, 2025)
Asthma is a chronic inflammatory disease of airways that worsens when exposed to certain risk factors such as chemical irritants and physical exertion. Influenza, commonly known as the flu, can worsen respiratory symptoms in asthma patients, leading to hospitalization and further exacerbation of asthma. Vaccination against influenza is thus crucial for these patients. A systematic review and meta-analysis showed 59–78%decrease in asthma attacks after influenza vaccination. (1) This reduction translates to fewer asthma exacerbations, emergency department visits, and hospital admissions. This not only leads to reduced medical expenditure but also significantly decreases out-of-pocket expenses incurred by patients. (2) Moreover, hospitalization for asthma exacerbations poses a risk of nosocomial infections—those acquired in healthcare settings—which can further lead to morbidity and mortality. (3) Thus, influenza vaccine results in significant decrease in the number of asthma attacks, leading to improved quality of living, lower healthcare cost with significant reduction in non-prescribed medical expenditure, shorter hospital stays,and thus a low risk of nosocomial infections. The prevalence of influenza vaccination remains low in Pakistan, according to a consensus statement. (4) The reasons for this lack of coverage are complex and multifactorial, but they include a lack of confidence among patients and healthcare providers in the efficacy and safety of vaccines. (5) With deteriorating Air Quality Index (AQI) in urban centers of Pakistan, it is crucial to start widespread vaccination of patients at risk that will decrease losses of both money and lives.